Phylogenetic placement of Tretospeira cheirospora in Phaeosphaeriaceae - Liu, Ning-Guo; Liu, Jian-Kui; Sun, Ya-Ru; Jumpathong, Juangjun (Phytotaxa, 2023)
A new hyphomycetous species, Tretospeira cheirospora, collected on decaying wood in a terrestrial habitat in northern Thailand is described and illustrated. It has macronematous, mononematous, erect, short, simple, brown to dark brown conidiophores, monotretic conidiogenous cells, and cheiroid, olivaceous brown to brown, distoseptate conidia composed of 4 columns and with an apical, hyaline, gelatinous sheath. Molecular data of Tretospeira are provided for the first time. The phylogenetic analysis of combined LSU and ITS sequence data shows that Tretospeira cheirospora belongs to Phaeosphaeriaceae and presents a distinct lineage which is sister to Banksiophoma australiensis. Hyphomycetous asexual morphs in Phaeosphaeriaceae and morphologically similar genera are compared and discussed.